Clinical outcomes of secondary prevention strategies for young patients with cryptogenic stroke and patent foramen ovale. Issue 4 (4th July 2017) - Danese, Alessandra; Stegagno, Chiara; Tomelleri, Giampaolo; Piccoli, Anna; Turri, Giulia; Carletti, Monica; Variola, Andrea; Anselmi, Maurizio; Mazzucco, Sara; Ferrara, Angela; Bovi, Paolo; Micheletti, Nicola; et al.
Abstract: Background The aim of this study was to compare the immediate and long-term clinical outcomes of medical therapy and percutaneous patent foramen ovale (PFO) closure as secondary prevention strategies in patients younger than 55 years of age presenting with cryptogenic stroke and PFO. Methods Between January 2006 and April 2015, all patients with the diagnosis of cryptogenic stroke and PFO were analysed and prospectively followed. Stroke was confirmed in 159 out of 309 patients (51%). In the remaining cases, other neurological conditions were found and therefore excluded from further analysis. Patients received PFO closure or medical therapy on the basis of a pre-specified algorithm. Primary outcome was the assessment of recurrent ischaemic events at follow-up. Results Percutaneous PFO closure was performed in 77 patients (48%) and 82 (52%) were treated medically. Mean follow-up was 51.6 ± 34.8 months. Two ischaemic strokes occurred in the medical group only (2.4% vs 0%; P = 0.16) and no complications related to the invasive procedure were observed. Conclusions The diagnosis of stroke in patients with PFO could be confirmed in 50% of cases only, underlining the importance of a multidisciplinary evaluation of these patients. A very low ischaemic recurrence rate was observed in the medical therapy group, suggesting that a personalized treatment based on a prespecified diagnostic algorithm yields good clinical results irrespective of the treatment modality. Given the low number of recurrences, larger cohorts may be needed to prove significant differences.